First reports of the psychological consequences of the SARS-CoV-2 pandemic. What appeared in the scientific literature between January and June 2020? - Marta Makara-Studzińska; Maciej Załuski; Katarzyna Adamczyk; Jakub Lickiewicz (Termedia Publishing House, 2021)
The SARS-CoV-2 pandemic can be perceived from a biopsychosocial perspective. The biological aspect focuses on groups particularly susceptible to infection, like the elderly, patients treated for severe somatic complaints, and carriers of the SARS-CoV-2 virus. The psychological aspect relates to the negative impact of social isolation and of the information chaos associated with the pandemic. The group of people at risk of developing psychological problems consists of psychiatric patients, persons in quarantine, relatives of patients hospitalized due to COVID-19, carriers of the SARS-CoV-2 virus, and socially lonely people. Hence, many people may experience episodic or chronic emotional disturbances. The social aspect draws attention to the negative psychological consequences of the gradually deteriorating economic situation of citizens and the cumulative multiple consequences of social isolation. The problem undertaken by the authors of the article was to recognize the psychological consequences of the first weeks of the SARS-CoV-2 pandemic in the human population. The article is of an overview nature. The literature used in the article came from the database MEDLINE between 1 January and 30 June 2020. The articles were obtained using the key words: SARS-CoV-2, mental health, and pandemics. The method of narrative analysis was used. This study combines the above-mentioned 3 aspects, showing the presumed long-term psychological consequences of a pandemic for the functioning of the individuals and society. The most important psychological consequences of a pandemic are explained, including the issue of high-risk groups. Probable risk factors for emotional disorders and psychological problems are described.